From family control to female leadership: Enhancing anti-corruption transparency in Indonesian corporations - Barokah, Zuni (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study explores how family ownership and board diversity, particularly the presence of female directors, influence the extent of anti-corruption disclosures among the largest publicly listed companies in Indonesia and whether female board members affect the impact of family on the disclosures. Grounded in agency theory, the research posits that family ownership limits the transparency of anti-corruption disclosures. Additionally, drawing on upper-echelon theory, it is hypothesized that female directors promote more transparent anti-corruption reporting, thereby mitigating the negative impact of family ownership.Design/Methodology/Approach: This study analyzed a dataset of 443 firm-year observations from Indonesian non-financial companies between 2018 and 2023 and employed an OLS regression model that controls industry effects and uses robust standard errors.Research findings: The results reveal that family ownership is associated with lower levels of anti-corruption disclosure transparency. However, the presence of female directors on boards increases the level of anti-corruption disclosures, helping to counteract this negative effect and enhance transparency. Theoretical contribution/ Originality: This study contributes to the literature on anti-corruption disclosures and offers valuable insights into the governance implications of family ownership and gender diversity on corporate boards.Practitioner/Policy implication: The findings highlight the importance of promoting gender diversity within corporate leadership, as it can play a crucial role in improving governance quality, particularly in the area of anti-corruption disclosures.Research limitation/Implication: The study did not have many alternative family firm measurements because of the limited data in Indonesia. Family firm data is difficult to trace.